PENERAPAN INTERVENSI SEMI FOWLER PADA PASIEN DENGAN MASALAH POLA NAFAS TIDAK EFEKTIF DI RUANG PICU RUMAH SAKIT IMMANUEL BANDUNG - Firmansyah, Agus (Institut Kesehatan Immanuel, 2025)
Diabetic Ketoacidosis (DKA) is an emergency condition due to hyperglycemia that can be life-threatening for clients with diabetes mellitus. As a result of various factors and characterized by narrowing of the airways, resulting in shortness of breath in patients. One thing that can be done is providing a Semi-Fowler position, which is an important way to restore respiration to normal and reduce shortness of breath significantly. The purpose of this study was to analyze the application of semi-fowler interventions with a medical diagnosis of diabetic ketoacidosis with nursing problems of ineffective breathing patterns at Immanuel Hospital, Bandung. The method used was a case study and data collection using interviews, observations and documentation. The results of the nursing care analysis obtained the main nursing problem in the patient, namely ineffective breathing patterns. Nursing interventions carried out to overcome the main nursing problem were to provide airway management with a semi-fowler position after the intervention, the problem of ineffective breathing patterns could be resolved, marked by respiration returning to normal and a decrease in the frequency of shortness of breath in patients. Therefore, it is hoped that this intervention can be collaborated with other interventions as one of the actions in carrying out comprehensive nursing care.